Pengembangan Model Pembelajaran Problem Solving Guna Meningkatan Kreatifitas Belajar Siswa SMK Negeri 7 Jakarta - Arief Nugroho Wibowo; Sri Mardiyati (Journal on Education, 2023)
The goal of a vocational school is to prepare students to have good moral character and work ethic, to improve their quality of life, and to have the skills needed in their chosen field. The school also aims to keep students up-to-date with technology and to train them to be productive workers. Learning requires creativity to be optimised in teaching in order to achieve the educational goals most effectively. However, creativity in learning often remains low among students. This study aims to see the development of a problem-solving teaching model (PS model). If we could see an increase in creativity in students' learning, this would be a research and development project testing the best in class XI at SMKN 7 Jakarta in the subject of entrepreneurship. The author suggests that the Problem Solving learning model contributes to increasing students' creativity in entrepreneurship lessons, and recommends that the model be developed further in subsequent lessons and subjects.